Homeopathic Medicines in the Management of Dermatophytosis (Tinea Infections): A Clinico-epidemiological Study with Pre–post Comparison Design - Dixit, Ashish Kumar; Javed, Danish; Srivastava, Amit; Bala, Renu; Giri, Nibha (Homeopathy, 2023)
Background Dermatophytosis is a common fungal infection of the skin and nails. Insufficient data exist regarding the clinico-epidemiological profile of dermatophytosis and the usefulness of individualized homeopathic medicines (IHMs) for patients visiting a homeopathy outpatient department (OPD).Objectives This article undertakes a clinico-epidemiological profiling of dermatophytosis and the usefulness of IHMs in its management.Methods This open-label, pre–post, comparative observational study was conducted in a homeopathy OPD from November 2018 to February 2020. IHMs were prescribed based on symptom totality and repertorization. A numeric rating scale (NRS) and the Dermatology Life Quality Index (DLQI) patient questionnaires were used, and results were analyzed using SPSS-IBM version 20.Results Data from a total of 103 patients, mean age 29.65 ± 15.40 years, were analyzed. Tinea cruris was the most common infection (29.1%), followed by tinea corporis (13.6%). After 3 months of treatment, significant reductions in NRS and DLQI scores were observed (8.51 ± 1.24 to 0.59 ± 0.83, p < 0.001, and 16.28 ± 5.30 to 1.44 ± 1.56, p < 0.001, respectively), with Sepia (15.5%), Sulphur (14.6%), Calcarea carbonica (11.7%), Natrum muriaticum (9.7%) and Bacillinum (8.7%) being the most frequently prescribed medicines. There was no significant correlation between occupation, sex, home location or marital status and the clinical types of dermatophytosis. No adverse events were reported.Conclusion T. cruris and T. corporis were prevalent dermatophytic infections. The decrease in NRS and DLQI scores associated with homeopathy indicates its usefulness as an integrative treatment option for dermatophytosis. Further research in larger and more diverse population samples is needed.
Keywords: clinico-epidemiology; dermatophytosis; homeopathy; ringworm